A requirement engineering approach for designing XML-view driven, XML document warehouses - Nassis, V.; Rajugan, Rajagopal; Dillon, Tharam S.; Rahayau, W. (IEEE, 2005)
The EXtensible Markup Language (XML) has emerged as the dominant standard in describing and exchanging data among heterogeneous data sources. The increasing presence of large volumes of data appearing in enterprise settings creates the need to investigate XML Document Warehouses (XDW) as a means of handling and analysing XML data for business intelligence. In our previous work, we proposed a conceptual modelling approach for the design and development of XDWs, with emphasis on capturing data warehouse requirements early in the design stage. To address this issue, in this paper, we explore a Requirement Engineering (RE) approach, namely the Goal-Oriented approach. We adopt and extend the notion of this approach and introduce the XDW Requirement Model. This focuses on deriving dimensions, as opposed to associating organizational objectives to the system functions, which is carried out by the traditional requirement engineering process.